A jeśli książka się nie sprzedawała? „Kreatywne” praktyki wydawniczo-księgarskie we Lwowie w XVIII wieku - Rusińska-Giertych, Halina (AUPC Studia ad Bibliothecarum Scientiam Pertinentia, 2021)
Although reading became generally more popular in the eighteenth century, not everyone read books. Discussions about books took place in aristocratic salons and at social meetings of rich noblemen, scholars and burghers, however, the lower classes were not exposed to books for quite some time. Readership, which increased mainly in bigger, important towns, was low in rural areas. Warsaw (due to the circles of scholars and writers, reforms of education, theatre, journalism, patrons and the offerings of publishing houses and booksellers) provided optimal conditions for the development of readership in Poland, yet even there, only the better-educated people engaged in reading. Because the Poles were not very interested in books, institutions which produced and distributed them began to encounter financial problems. Publishing houses and bookstores in Lvov also had problems with disposing of excessive copies (printed or imported for sale). They had to devise various strategies to inform their clients about the books they offered or persuade them to buy them. Advertising was not always successful and unwanted books remained stored and unsold for long periods. Those who had contributed to their publication now had to consider how to deal with this problem and were obliged to undertake various “creative” book-selling strategies. This article describes the solution employed by the printing house and bookstore owned by the Pillers as well as the bookstore of Karol Bogusław Pfaff in Lvov, namely the practice of reissuing books.